Immobilization of a Bifidobacterial Endo-ß-N-Acetylglucosaminidase to Generate Bioactive Compounds for Food Industry - Pekdemir, Burcu; Duman, Hatice; Arslan, Ayşenur; Kaplan, Merve; Karyelioğlu, Melda; Özer, Tolgahan; Kayılı, Hacı Mehmet; Salih, Bekir; Henrick, Bethany M.; Duar, Rebbeca M.; Karav, Sercan (Frontiers in Bioengineering and Biotechnology, 2022)
Conjugated N-glycans are considered as next-generation bioactive prebiotic compounds due to their selectively stimulation of beneficial microbes. These compounds are glycosidically attached to proteins through N-acetylglucosamines via specific asparagine residue (AsN-X-Ser/Thr). Certain bacteria such as Bifidobacterium longum subspecies infantis (B. infantis) have been shown to be capable of utilizing conjugated N-glycans owing to their specialized genomic abilities. B. infantis possess a unique enzyme, Endo-ß-N-acetylglucosaminidase (EndoBI-1), which cleaves all types of conjugated N-glycans from glycoproteins. In this study, recombinantly cloned EndoBI-1 enzyme activity was investigated using various immobilization methods; (1) adsorption and (2) entrapment-based alginate immobilization, (3) SulfoLink and (4) AminoLink-based covalent bonding immobilization techniques were compared to develop an optimum application of EndoBI-1 into food processes. The yield of enzyme immobilization and the activity of each immobilized enzyme by different approaches were investigated. The N-glycans released from lactoperoxidase (LPO) using different immobilized enzyme forms were characterized using MALDI-TOF mass spectrometry (MS). Expectedly, regardless of the techniques, the enzyme activity was decreased after immobilization methods. The enzyme activity of adsorption and entrapment-based alginate immobilization was found to be 71.55% +/-0.6, 20.32% +/-3.18, whereas the activity of AminoLink and SulfoLink-based covalent bonding immobilization was found to be 58.05 +/-1.98 and 47.49% +/-0.30 compared to the free form of the enzyme, respectively. However, extended incubation times recovered achieved similar activity to the free form. More importantly, each immobilization method resulted in same glycan profile containing eleven different N-glycan structures from a model glycoprotein LPO based on MALDI-TOF MS analysis. The glycan data analysis suggests that immobilization of EndoBI-1 is not affecting the enzyme specificity, which enables full glycan release without a limitation. Hence, different immobilization methods investigated in this study can be chosen for the effective enzyme immobilization to obtain bioactive glycans. These findings highlight further optimization of these methods can be a promising approach for future processing scale-up and commercialization of EndoBI-1 and similar enzymes.